2020
DOI: 10.1080/19490976.2020.1785804
|View full text |Cite
|
Sign up to set email alerts
|

Extremely preterm neonates have more Lactobacillus in meconium than very preterm neonates – the in utero microbial colonization hypothesis

Abstract: Growing evidence suggests that maternal microbiota can influence the neonates' gut colonization. However, the mechanisms of vertical bacterial transmission remain poorly defined. We believed that the first colonizers of the newborn come from the mother's gut and vagina during pregnancy and that this is independent of the mode of delivery. We conducted an observational longitudinal study to evaluate the link between the maternal gut microbiota and the meconium's microbiota in extremely and very preterm neonates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The prevailing paradigm in obstetrics has been the sterile womb hypothesis. However, studies have identified the presence of bacteria in the amniotic fluid, placenta, umbilical cord, 91 , 92 and meconium of PT, 93 and full-term infants. 94 This suggests that colonization of the gastrointestinal tract begins in utero .…”
Section: Discussionmentioning
confidence: 99%
“…The prevailing paradigm in obstetrics has been the sterile womb hypothesis. However, studies have identified the presence of bacteria in the amniotic fluid, placenta, umbilical cord, 91 , 92 and meconium of PT, 93 and full-term infants. 94 This suggests that colonization of the gastrointestinal tract begins in utero .…”
Section: Discussionmentioning
confidence: 99%
“…Microbiota results are expressed as log10 16S rRNA gene copies/10 ng of DNA. All of the analyses were conducted using the appropriate negative controls, as previously described [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although the idea of whether the prenatal environment is sterile remains questionable (Fricke and Ravel, 2021), the presence of microbiota has been detected in meconium by using either nextgeneration sequencing (NGS) or real-time PCR (Morais et al, 2020;Hiltunen et al, 2021;Klopp et al, 2022). The meconium FIGURE 1 | The developmental trajectory and comparisons of full-term and preterm infants in the first 1000 days after birth.…”
Section: Meconium: Birthmentioning
confidence: 99%
“…Although the idea of whether the prenatal environment is sterile remains questionable ( Fricke and Ravel, 2021 ), the presence of microbiota has been detected in meconium by using either next-generation sequencing (NGS) or real-time PCR ( Morais et al, 2020 ; Hiltunen et al, 2021 ; Klopp et al, 2022 ). The meconium microbiota normally exhibits large between-individual variation, which is influenced by gestational age at birth ( Klopp et al, 2022 ).…”
Section: Development Of Gut Microbiota In Preterm Birthmentioning
confidence: 99%